The provision of hospital at home care: Results of a national survey of UK hospitals. Issue 12 (11th October 2021) - Knight, Thomas; Harris, Ciara; Mas, Miquel À.; Shental, Omri; Ellis, Graham; Lasserson, Daniel
Abstract: Background: Hospital at home (HaH) replicates elements of hospital‐based care in the community, to facilitate the safe management of a broad spectrum of acute illness in the patient's usual environment. The extent to which this model of care has been adopted in the United Kingdom is unknown. Methods: The Society for Acute Medicine Benchmarking Audit is a day of care survey undertaken annually within the United Kingdom. Participation is open to all hospital in the United Kingdom receiving acutely unwell medical patients. A questionnaire is used to collect hospital‐level data on the structure and organisation of acute care delivery. The survey included questions designed to quantify the number of hospitals that offered HaH. When present, further questions were asked to clarify the characteristics of the HaH service in terms of workforce, range of diagnostic test and interventions. This information was used to build a picture of HaH service provision on a national scale. Results: A total of 130 hospitals contributed organisational data to SAMBA19. The capability to refer to a hospital at home service was recognised by 46.9% (n = 61) of units. The majority of these services, 83.3% (n = 50) were nurse‐led. The capability to provide a physician review at home was reported in 23.3% (n = 14). The majority of services could provide intravenous antibiotics at home, but access to other simple interventions, such as intravenous diuretics or acute supplemental oxygen, is limited. Conclusion: At present, few acute hospitals for consitency in the United Kingdom have access to a hospital at home service capable of replicating essential elements of inpatient care. Our study suggests organisational change in acute care delivery and significant investment would be required to establish equal access to hospital‐at‐home care within the United Kingdom